STUDENTS’ PERCEPTION IN LEARNING EXTENSIVE LISTENING BY USING CARTOON MOVIES - Susanto Susanto; Deri Sis Nanda; Yanuarius Yanu Dharmawan; Tri Nun Hartini; Linda Septiyana; Bagus Firmansyah (Universitas Bandar Lampung, 2022)
Extensive listening is a way to practice listening skill thoroughly. Listening to various recordings, videos, and interviews on the same topic will help to get context in a real situation, and will help to learn more vocabulary. The objective of this research was to find out students’ perceptions in learning extensive listening by using cartoon movies. This study used a qualitative method. The research was done at SMK Trisakti Jaya Bandar Lampung for the 10th grade students (N=38). Data gathering was done by conducting observation, questionnaire and interview. The result showed that they agree learning English through extensive listening by using cartoon movies as the listening materials help them a lot to develop their listening skill. Based on the observations, questionnaires and interviews, it can be concluded that most of the students think that it is very helpful, and faster for them in learning English with extensive listening technique. Most students thought that learning extensive listening by using cartoon movies can be carried out in the learning process.